LPS-Activated Monocytes Are Unresponsive to T4 Phage and T4-Generated Escherichia coli Lysate - Bocian, Katarzyna; Borysowski, Jan; Zarzycki, Michał; Wierzbicki, Piotr; Kłosowska, Danuta; Weber-Dąbrowska, Beata; Korczak-Kowalska, Grażyna; Górski, Andrzej (Frontiers in Microbiology, 2016)
A growing body of data shows that bacteriophages can interact with different kinds of immune cells. The objective of this study was to investigate whether T4 bacteriophage and T4-generated Escherichia coli lysate affect functions of monocytes, the key population of immune cells involved in antibacterial immunity. To that end we evaluated how T4 and E. coli lysate influence the expression of main costimulatory molecules including CD40, CD80 and CD86, TLR2, TLR4 on monocytes, as well as the production of IL-6 and IL-12 in cultures of peripheral blood mononuclear cells (PBMCs). Separate experiments were performed on unactivated and LPS-activated PBMCs cultures. Both studied preparations significantly increased the percentage of CD14+CD16-CD40+ and CD14+CD16-CD80+ monocytes in unactivated PBMCs cultures, as well as the concentration of IL-6 and IL-12 in culture supernates. However, neither purified T4 nor E. coli lysate had any significant effect on monocytes in LPS-activated PBMCs cultures. We conclude that LPS-activated monocytes are unresponsive to phages and products of phage-induced lysis of bacteria. This study is highly relevant to phage therapy because it suggests that in patients with infections caused by Gram-negative bacteria the administration of phage preparations to patients and lysis of bacteria by phages are not likely to overly stimulate monocytes.